KAJIAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TOMAT CHERRY (Solanum lycopersicum var. cerasiforme): pupuk organik, pertumbuhan, tomat cherry. - Banafsya, Novia Banafsya; Santosa, Sartono Joko; Siswadi, Siswadi (innofarm, 2024)
The research titled "Study of Doses of Organic Fertilizers on the Growth and Yield of Cherry Tomatoes (Solanum lycopersicum var. cerasiforme)" sought to find out how different organic fertilizer dosages affected cherry tomato (Solanum lycopersicum var. cerasiforme) growth and yield. The research was carried out in the TPH Tohudan Seed Garden between December 2022 and March 2023. The experimental design used was a fully randomized design (CRD) with a single factor pattern, with each combination of treatments repeated 3 times. The parameters included three categories of organic fertilizers: (1) Goat manure is available in three different quantities per polybag: 150 grams, 300 grams, and 450 grams. (2) Chicken manure is available in three different quantities per polybag: 225 grams, 450 grams, and 675 grams. (3) Vermicompost fertilizer is available in three different quantities per polybag: 300 grams, 600 grams, and 900 grams. (4) There is also an option to choose no fertilizer. The observational data were subjected to statistical analysis using analysis of variance (ANOVA), followed by further tests using Honest Significant Differences (HSD) at a significance level of 5%. The parameters that were recorded consisted of plant height, leaf count, stem circumference, branch count per plant, fruit count per plant, fruit weight, and fruit diameter. The application of chicken dung at a dosage of 675 grams per polybag produced the most favorable outcomes.